2010
DOI: 10.1068/i0382
|View full text |Cite
|
Sign up to set email alerts
|

Yarbus, Eye Movements, and Vision

Abstract: The impact of Yarbus's research on eye movements was enormous following the translation of his book Eye Movements and Vision into English in 1967. In stark contrast, the published material in English concerning his life is scant. We provide a brief biography of Yarbus and assess his impact on contemporary approaches to research on eye movements. While early interest in his work focused on his study of stabilised retinal images, more recently this has been replaced with interest in his work on the cognitive inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
117
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(123 citation statements)
references
References 36 publications
5
117
0
1
Order By: Relevance
“…His experiments measuring eye movements toward "The Unexpected Visitor" have demonstrated that different tendencies of gaze distributions can be observed according to the given tasks (e.g., free examination, give the ages of the people). The same results have been reported in the tutorial by Tatler et al [18]. Moreover, The tutorial by Hayhoe et al [19] presents some examples that human attention can be oriented to task-relevant locations rather than salient locations in the case humans are given some tasks.…”
Section: Relationship Between Visual Attention Human Intentions Andsupporting
confidence: 71%
“…His experiments measuring eye movements toward "The Unexpected Visitor" have demonstrated that different tendencies of gaze distributions can be observed according to the given tasks (e.g., free examination, give the ages of the people). The same results have been reported in the tutorial by Tatler et al [18]. Moreover, The tutorial by Hayhoe et al [19] presents some examples that human attention can be oriented to task-relevant locations rather than salient locations in the case humans are given some tasks.…”
Section: Relationship Between Visual Attention Human Intentions Andsupporting
confidence: 71%
“…Although his findings were based on only one observer, they have been replicated and extended over the last decade (see DeAngelus & Pelz, 2009; Tatler, Wade, Kwan, Findlay, & Velichovsky, 2010). These studies suggest that eye movement patterns convey information about the task a person was performing while viewing the stimulus.…”
Section: Introductionmentioning
confidence: 88%
“…It is worth noting that methods sharing similarities with iMap have been introduced by various authors before us (e.g., Barrington, Marks, Hsiao, & Cottrell, 2008;Bruce & Tsotsos, 2009;Buchan, Paré, & Munhall, 2007;Harding & Bloj, 2010;Henderson, 2003;Kita et al, 2010;Pomplun, Ritter, & Velichkovsky, 1996;Tatler, Wade, Kwan, Findlay, & Velichkovsky, 2010;Torralba, Oliva, Castelhano, & Henderson, 2006;Wooding, 2002). Here, we briefly present the characteristics that few of these methods share with iMap and what differentiate them from it.…”
mentioning
confidence: 99%
“…Note that using a Gaussian smoothing on fixations, weighted by their durations, is not novel per se, and heat map representations have become very popular in the last few years (see, e.g., Barrington et al, 2008;Bruce & Tsotsos, 2009;Buchan et al, 2007;Harding & Bloj, 2010;Henderson, 2003;Kita et al, 2010;Tatler et al, 2010;Torralba et al, 2006;Watanabe, Matsuda, Nishioka, & Namatame, 2011;Wooding, 2002). However, in most of these cases, the heat maps were used only for illustration purposes.…”
mentioning
confidence: 99%